2014
DOI: 10.5194/acp-14-7847-2014
|View full text |Cite
|
Sign up to set email alerts
|

Observed characteristics of dust storm events over the western United States using meteorological, satellite, and air quality measurements

Abstract: Abstract. To improve dust storm identification over the western United States, historical dust events measured by air quality and satellite observations are analyzed based on their characteristics in data sets of regular meteorology, satellitebased aerosol optical depth (AOD), and air quality measurements. Based on the prevailing weather conditions associated with dust emission, dust storm events are classified into the following four typical types:(1) The key feature of cold front-induced dust storms is their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 24 publications
(33 reference statements)
2
36
0
Order By: Relevance
“…), it is imperative to minimize the risk of wind erosion and dust generation. The atmospheric residence time for particulate dust (PM10) can range from seconds to weeks (Lei and Wang , Reynolds et al. ), suggesting that effective control of dust sources can have rapid impacts on atmospheric pollution levels.…”
Section: Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…), it is imperative to minimize the risk of wind erosion and dust generation. The atmospheric residence time for particulate dust (PM10) can range from seconds to weeks (Lei and Wang , Reynolds et al. ), suggesting that effective control of dust sources can have rapid impacts on atmospheric pollution levels.…”
Section: Responsesmentioning
confidence: 99%
“…With a warmer, drier, and more variable future climate predicted for much of the southwestern United States, including more extreme droughts (Seager 2007, Cook et al 2015, Ault et al 2016, it is imperative to minimize the risk of wind erosion and dust generation. The atmospheric residence time for particulate dust (PM10) can range from seconds to weeks (Lei andWang 2014, Reynolds et al 2016), suggesting that effective control of dust sources can have rapid impacts on atmospheric pollution levels. A comprehensive dust-management strategy should therefore include a combination of (1) eliminating or reducing the intensity or extent of land-use activities that produce dust; (2) implementing restoration or reclamation strategies that promote ecosystem resilience to wind erosion; (3) accounting for landscape heterogeneity for both planning potential dust-producing land uses and targeting restoration/reclamation actions to maximize dust abatement; and (4) encouraging research and monitoring to further understand the interaction of eolian processes, pressures, and ecosystems.…”
Section: Responsesmentioning
confidence: 99%
“…This region includes sources from the arid Southwest (e.g., the Mojave, Great Basin, Sonoran, and Chihuahuan Deserts) and gives rise to some of the highest aeolian dust concentrations in the United States [ Prospero et al ., ]. The Southwest has been the focus of many local and regional studies to characterize dust concentrations that peak in spring and early summer due to synoptic‐scale meteorological patterns that transport dust across the region and continent [e.g., Brazel and Nickling , ; Stout and Lee , ; Novlan et al ., ; Park et al ., ; Lee et al ., ; Rivera Rivera et al ., ; Hahnenberger and Nicoll , ; Tong et al ., ; Lei and Wang , ; Reynolds et al ., ]. Fewer studies have reported dust concentrations in the central and northern Great Plains regions [e.g., Hand et al ., , ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of the dust characterization studies that have occurred in the Southwest and other regions of the United States have used diverse types of data, such as column optical depth from satellite [e.g., Ginoux et al ., ], low‐visibility meteorological records [e.g., Okin and Reheis , ; Novlan et al ., ], ground‐based ion deposition [e.g., Brahney et al ., ; Sorooshian et al ., ], and other ground‐based assessments using different particle size ranges and dust definitions [e.g., Reheis and Urban , ; Tong et al ., ; Neff et al ., ; Lei and Wang , ; Reynolds et al ., ]. In addition, many studies focus only on details of episodic events [e.g., Lee et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the knowledge of these dust storms, Lei and Wang (2014) analyzed the meteorological characteristics of a set of historical dust transport episodes measured by means of AQ and satellite observations, finding that the dust mass concentrations captured by in situ measurements are consistent with the variations of AOT(0.55 μm) retrieved from local ground-based radiometer and satellite observations. Four typical dust storm cases were considered: (i) case D1, regarding a cold front-induced dust storm characterized by rapid processes and strong dust emissions; (ii) case D2, caused by meso-to small-scale weather systems and presenting a very high emission level; (iii) case D3, regarding a dust storm caused by tropical disturbances and yielding a stronger particle concentration of dust for an emission 1) SPRINTARS is a global aerosol transport-radiation model named "Spectral Radiation-Transport Model for Aerosol Species," which is coupled with an atmospheric general circulation model including a mixed layer ocean and simulates changes in the meteorological field due to the aerosol direct and indirect radiative effects produced by the main components of tropospheric aerosol.…”
Section: Dust Storms In the Southwestern United Statesmentioning
confidence: 99%